Utilization of rice water and vegetable waste liquid fertilizer for melon growth at MAC - Meisya Rismasari Utami; Annisa Khumaira; Parijo Parijo (International Journal of Health Science and Technology, 2026)
The increasing demand for fertilizers in melon cultivation, combined with the high cost and limited availability of commercial fertilizers, presents a major challenge to sustainable agricultural production, particularly for small-scale farmers. In addition, the improper disposal of household organic waste, such as rice washing water and vegetable waste, contributes to environmental pollution. This study aimed to evaluate the effectiveness of liquid organic fertilizer (LOF) produced from rice washing water and vegetable waste in promoting the growth of melon plants (Cucumis melo L.) cultivated in the open field at the Muhammadiyah Agribusiness Center (MAC). An experimental design was applied using four treatments: control, rice water LOF, vegetable waste LOF, and a combination of both. Plant height and leaf number were measured twice weekly over four observation periods, and the data were analyzed descriptively using Microsoft Excel. The results showed that rice water LOF produced the highest growth performance, with plant height reaching 12.5 cm and nine leaves at the end of the study. Vegetable waste LOF also enhanced plant growth compared to the control, while the combined treatment provided no additional benefits. These findings demonstrate the potential of household organic waste as a low-cost and environmentally friendly fertilizer source. This study contributes to sustainable agriculture by providing practical evidence for waste valorization and offers societal benefits through reduced production costs, improved waste management, and support for environmentally responsible farming practices.